VD_FINDINFO HC / 2011 / 655 vom 5. Oktober 2011 - VD Tribunal cantonal (2011)
HYPOTHÈQUE LÉGALE DES ARTISANS ET ENTREPRENEURS, DÉLAI | 837 al. 1 ch. 3 CC, 839 al. 2 CC, 209 CPC, 308 al. 1 let. b CPC (CH), 310 CPC (CH), 404 CPC (CH)